An annotated checklist of fish species described from the Philippines - Rodulf Anthony T. Balisco; Te-Yu Liao (ZooKeys, 2025)
A comprehensive list of fish species collected from Philippine waters and taxonomically described from 1770 to 2024 is herein compiled and presented. A total of 1212 species from 156 families were described, of which 828 from 135 families are currently considered valid, 349 invalid, and 34 with unknown or uncertain status. There are also 228 species currently recorded only in Philippine waters, with 85 species found only in estuarine and freshwater areas, and 143 species in the marine habitats. The type information of these species is also listed together with their current valid names and authorships. The checklist also includes approximately 3842 lots containing 12549 specimens scattered in different museums, including 966 holotypes/lectotypes, 2654 lots of paratypes/paralectotypes, 216 lots of syntypes, and 15 lots of neotypes. Forty-five lots were un-cataloged, while approximately 324 lots were believed to have been lost or destroyed during World War II.